From Crowdsourcing Journalism to the Platformization of News: A Framework for the Analysis of Citizens' Collaboration, Emulation and Remix Practices in Social Media - Crespo, M.; Sepúlveda, R.; Moreno, J.; Álvares, Cláudia; Cardoso, G. (SIXTH INTERNATIONAL WORKSHOP ON ENTREPRENEURSHIP, ELECTRONIC AND MOBILE BUSINESS, 2022)
The goals are threefold: to try to understand how citizens interact with journalism in Europe, to try to categorize those interactions and to present case studies from different countries which can be considered as examples of best practices. To do so, we present a brief contextualization of journalism and citizen journalism, and a conceptual approach to three major categories of interaction, practices, and the use/reuse of journalistic content by citizens. We have taken as our starting point citizens’ engagement with journalism as both product and content: citizens collaborate with journalists in content production, citizens emulate journalistic practices, and citizens use/reuse journalism to contribute to public discourse and democracy. The report further develops a synoptic analysis of professional and user-generated news content, so as to provide us with a better understanding of the potentialities, limits, and reliability of so-called citizen journalism. A selection of positive cases is expounded on, aiming to be brought to the attention of policymakers.